Lonely planet : Myanmar - Allen, John; Smith, Allen John; Smith, Jamie (Victoria : Lonely Planet, 2014)
Lonely Planet Myanmar (Burma) is your passport to the most relevant, up-to-date advice on what to see and skip, and what hidden discoveries await you. Be dazzled by Buddhist architecture in Yangon, explore Bagan's amazing plain of ancient temples, or hike to the floating gardens and markets of Inle Lake; all with your trusted travel companion. Get to the heart of Myanmar and begin your journey now!
Keywords: Guidebook -- Burma -- Asia